A scientific review on disabled-friendly educational environment for disabilities student in Malaysia - Ismail, Faisal Husen (Penerbit UTHM, 2023)
The increasing number of Persons with Disabilities (PWDs) in Malaysia, as registered with the Department of Social Welfare until the end of 2020, estimated at 570,000, requires attention. PWDs are part of Malaysian society and should be granted equal rights and opportunities to live their lives easily. However, achieving this equality is not an easy task today. PWDs face various factors and challenges due to negative attitudes and discrimination deeply ingrained in society. Therefore, this study aims to explore the facilities and inclusivity in higher education for PWDs. It presents an exploratory study based on selected previous research regarding higher education for students with special needs in Malaysia. The research utilized a selection approach of 10 chosen articles to explore issues, management, and implementation efforts to create a PWD-friendly environment. The study found that educational facilities at the higher education level have been established, such as specially constructed parking spaces for PWDs. The study suggests the need for further improvements in other infrastructural aspects, such as wheelchair-friendly pathways, special routes for the visually impaired, and so on. The success of inclusive higher education for PWDs should involve a proactive environment in combating the neglect of PWDs in national development. Hopefully, these ideas can contribute to the construction of an inclusive environment within educational institutions. The study also suggests future research on the moral aspects of society towards PWDs.